Иван Гончаров в украинском литературоведческом пространстве - Dzyk, Roman (Ústav slavistiky FF MU, 2021)
Представлен актуальный контур украинского гончарововедения. Рассматриваются история и современное состояние изучения творчества Ивана Гончарова в Украине. Представлены основные векторы украинской литературоведческой рецепции русского классика. Внимание уделяется монографическим и диссертационным исследованиям, также включен обзор научной периодики. Отдельно рассматриваются украинские переводы и издания произведений писателя. Отмечаются возможные перспективные направления развития современного украинского гончарововедения. The article under studies deals with some significant issues of Ukrainian “Goncharov Studies”. It regards the history and contemporary state of investigation of Ivan Goncharov’s creative activities in Ukraine. It also covers main vectors of the Ukrainian literary reception of the Russian classic. Particular emphasis has been laid on monographic and dissertation research, as well as on a review of scientific periodicals. Ukrainian translations and editions of the writer’s works are considered separately. In addition, the possible perspective directions of development of modern Ukrainian ”Goncharov Studies” have been pointed out.
Ivan Goncharov in Ukrainian Literary Studies
Keywords: Иван Гончаров; гончарововедение; украинское гончарововедение; украинское литературоведческое пространство; украинская русистика; литературоведческая историография; Ivan Goncharov; “Goncharov Studies”; Ukrainian “Goncharov Studies”; Ukrainian Literary Studies; Ukrainian Russian Studies; Literary Historiography